Preclinical pharmacokinetics, interspecies scaling, and pharmacokinetics of a Phase I clinical trial of TTAC-0001, a fully human monoclonal antibody against vascular endothelial growth factor 2 - Lee WS; Shim SR; Lee SY; Yoo JS; Cho SK (Dove Medical Press, 2018)
Weon Sup Lee,1 Sang Ryeol Shim,1 Seon Young Lee,1 Jin San Yoo,1 Sung Kweon Cho2 1PharmAbcine, Inc., Daejeon, Republic of Korea; 2Department of Health Sciences and Technology, SAIHST, Sungkyunkwan University, Seoul, Republic of Korea Background: VEGF is a highly selective mitogen that serves as the central regulator of tumor angiogenesis by mediating endothelial proliferation, permeability, and survival. Tanibirumab (TTAC-0001) is a fully human IgG1 monoclonal antibody derived from a fully human naïve single-chain variable fragment (ScFv) phage library that was developed to inhibit the effects of VEGF in the treatment of solid tumors, especially those of the brain. Methods: In the present study, we conducted intravenous pharmacokinetic studies of TTAC-0001 in mice, rats, and cynomolgus monkeys. At the doses studied (3 mg/kg, 10 mg/kg, 30 mg/kg), TTAC-0001 exhibited dose proportionality in mice and monkeys. At a dose of ~10 mg/kg, the clearance of TTAC-0001 from serum was 0.017 mL/h in mice, 0.35 mL/h in rats, and 2.19 mL/h in cynomolgus monkeys, and the terminal half-life ranged from 20–30 h among the three species. Pharmacokinetic data in mice, rats, and cynomolgus monkeys were used to predict the pharmacokinetics of TTAC-0001 in humans using allometric scaling. The predicted serum clearance of TTAC-0001 in humans was 102.45 mL/h and the terminal half-life was 27.52 h. Results: The maximum life span-corrected clearance value was 72.92 mL/h. The observed clearance in humans was more similar to the predicted scaled clearance. Conclusion: We investigated the pharmacokinetics of TTAC-0001 in mice, rats, and cynomolgus monkeys after intravenous administration. At the doses studied, TTAC-0001 exhibited dose proportionality in mice and monkeys. The scaled pharmacokinetics of TTAC-0001 reported here was useful for designing first-in-human studies. Allometric scaling in the therapeutic antibody is feasible. Keywords: VEGF2, tanibirumab, pharmacokinetics, allometry, clearance, biodistribution